iBid: A Competitive Bidding Environment for Multiscale Tailor - Muhaini Othman; Siti Najiha Shamsudin; Mohd Hafizul Afifi Abdullah; Munirah Mohd Yusof; Rozlini Mohamed (Society of Visual Informatics, 2017)
Nowadays, various online auction web services are available, allowing people to bid on items to be purchased at a competitive price. The same approach is applicable to allow people to bid on projects on Freelancer website. Here, we present an environment for customers to publish a project online, whereby marketers are able to bid on projects, called the iBid system. The iBid system demonstrates an application of bidding system which is capable of assisting customers find local tailors according to three criteria namely location, type of sewing and cost. Reversed auction mechanism is used where the customer will control the business. The prototyping methodology approach has been used to develop the system running on a PHP server and a MySQL database.